2021
DOI: 10.1186/s43094-021-00215-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative disorders associated with genes of mitochondria

Abstract: Background Over the last decade, aggregating evidences suggested that there is a causative link between mutation in gene associated with mitochondrial dysfunction and development of several neurodegenerative disorders. Main text Recent structural and functional studies associated with mitochondrial genes have shown that mitochondrial abnormalities possibly lead to mitochondrial dysfunction. Several studies on animal models of neurodegenerative dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Alongside maintaining healthy lysosomal functionality, ATP13A2 also plays a role in maintaining mitochondrial function. ATP13A2-deficient models exhibit mitochondrial dysfunction such as reduced membrane potential and ATP production, increased mitochondrial mass, fragmentation and reactive oxygen species (ROS) production [119]. Rotenone, a pesticide and mitochondrial complex I inhibitor that is an environmental Parkinson's disease risk factor, leads to mitochondrial ROS and toxicity causing cell death that can be attenuated upon ATP13A2-mediated PA transport [120].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Alongside maintaining healthy lysosomal functionality, ATP13A2 also plays a role in maintaining mitochondrial function. ATP13A2-deficient models exhibit mitochondrial dysfunction such as reduced membrane potential and ATP production, increased mitochondrial mass, fragmentation and reactive oxygen species (ROS) production [119]. Rotenone, a pesticide and mitochondrial complex I inhibitor that is an environmental Parkinson's disease risk factor, leads to mitochondrial ROS and toxicity causing cell death that can be attenuated upon ATP13A2-mediated PA transport [120].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…To date, many studies on NDDs have shown different features of neurodegeneration, such as cell viability reduction, genetic mutations, gene expression alterations, and cellular function impairment [95][96][97]. To understand the different cellular processes in NDDs, cell health has been evaluated using several methods, including morphological analysis, viability assays, metabolic assays, and gene expression analysis [98][99][100], because cell quality directly affects cell functionality [101,102].…”
Section: Analysis Of the Quality And Differentiation Ability Of Hbm-mscsmentioning
confidence: 99%
“…In the ageing brain, misfolded protein accumulates and leads to metabolic loss, oxidative stress-induced damage, and synapse dysfunction. In AD, oxidative damage is indicated by high levels of DNA oxidation products such as 8-hydroxydeoxyguanosine in the brain cell nucleus and mitochondria [6][7][8].…”
Section: Introductionmentioning
confidence: 99%